Anomalous nature of outbursts of black hole candidate 4U 1630−472. Issue 1 (13th December 2021) - Chatterjee, Kaushik; Debnath, Dipak; Bhowmick, Riya; Nath, Sujoy Kumar; Chatterjee, Debjit
ABSTRACT: The Galactic black hole candidate (BHC) 4U 1630−472 has gone through several outbursts (13 to be particular) in the last two and a half decades starting from the RXTE era till date. Like the outbursts of other transient BHCs, the outbursts of this source show variations in duration, peak numbers, highest peak flux, etc. However, unlike other soft X-ray transients, this source showed outbursts of two types, such as normal and super. The normal outbursts of duration ∼100−200 d are observed with an average recurrence or quiescence period of ∼500 d. The super outbursts of duration ∼1.5−2.5 yr, consist of more than one normal outburst and one mega outburst. We make an effort to separate the flux contributions of the normal and mega components from the super outbursts, and try to understand the nature of evolution of both types (normal and mega) of outbursts, based on the quiescent period prior to the outbursts. Archival data of RXTE or ASM from 1996 January to 2011 June, and MAXI or GSC from 2009 August to 2020 July are used for our study. Based on the variations of various properties of both the normal and mega outbursts, we think that this BHC is a special source which may contain two companions. Two companions might be responsible for two types of outbursts.